Mengembangkan Permainan Tongkat Estafet untuk Meningkatkan Sosial Emosional Anak Usia 5-6 Tahun - Baik Nilawati Astini; I Made Suwasa Astawa; I Nyoman Suarta; Miranda Yuspiaya (Indonesian Journal of Elementary and Childhood Education, 2021)
This research was motivated by the lack of developing the ability of the emotional social child in the game of sticks in the village in the village of the West Lombok Geraga. The purpose of this study was to find out how to play the right relay stick game to improve the emotional social capabilities of children aged 5-6 years. This development research uses data analysis of qualitative descriptive. The subject in this study was 8 children aged 5-6 years. The data collection technique in this study was carried out by observation and documentation. Data analysis using qualitative descriptive. This research was conducted as an effort to improve the emotional social development of children aged 5-6 years through the game sticks conducted in three (3) trial phases in 3 meetings and a percentage increase in the subject. The results of the research obtained at 8 subjects for 3 meetings increased by developing very well in group 1, namely subject 1 AG reached 100% BSB value, subject 2 BA reached 96.15% BSB value, subject 3 I reached 92.30% BSB value, and subject 4 AR reached 96.1 The conclusion of the results of the study is that if the steps of the relay stick players are carried out properly and correctly it can improve the emotional social capacity of children aged 5-6 years in Mendagi Gerung Village.